Effect of Exposure to Cement Dust on Peak Expiratory Flow Rate of Cement Factory Workers (Journal of Chittagong Medical College Teachers' Association, 2021)
Background: Pollutants exerted from different industries are hazardous for both employees and the environment. Though cement industry is playing a key role in economic growth but is a major source of air pollution. Its exposure affects pulmonary functions due to alteration of structural and functional properties of lung. Peak Expiratory Flow Rate (PEFR) is a simple, less expensive pulmonary function test which can be done by spirometer to detect obstructive changes in the respiratory tract.This study is aimed to assess the effect of cement dust on peak expiratory flow rate of workers, those who are exposed to cement dust directly in cement factory.Materials and methods: This case control study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram in collaboration with Heidelberg Cement Bangladesh Ltd at Chattogram from January 2018 to December 2018. Total 88 male workers with age ranged from 20 to 45 years were included in this study by consecutive sampling method. Case group workers were selected from those who were working at least two years in direct contact of cement dust and control group were from office workers of same factory those who were not in direct contact of cement. 44 subjects were included in each group. A predesigned data collection form was filled up by the researcher,which contained information regarding general physical status, job history, present and past disease, drug history of workers. Individual’s height, weight was measured and BMI was calculated. PEFR was assessed by a portable digital spirometer (Chestgraph HI-101, Japan) in upright sitting posture. After compiling data,statistical analyses were done by using SPSS version Windows 25. Unpaired student's 't' test was done for statistical analysis.Results: PEFR of Control and Case group was 7.84±2.21 L/sec and 5.73±1.79 L/sec respectively. In this study Case group showed significant reduction of PEFR (p